Optimization of catadioptric location for a CCTV system in an indoor space - Jaafar, Haryati (2011)
Proper placement of cameras is an important design requirement in security camera application. Camera placement has a significance impact on the overall area coverage. The layout of security location, camera parameters and strategy of camera placement are important design consideration. This thesis focuses on maximizing the coverage area of a security camera in the IC Design Laboratory of Universiti Putra Malaysia. The current perspective stationary camera located near the lift entrance is not adequate. Thus, the use of a different camera system using catadioptric that combines lens and mirror with 360° field of view to replace the existing camera is proposed. Given the 2D plan layout in IC Design Laboratory, five cameras are mounted on the ceiling, each with a radius of coverage of 3m. The goal of research is to determine the optimal location of the cameras that covers maximum area of interest. Two different strategies, namely the set cover strategy and the set packing strategy are applied and compared to evaluate their effectiveness. The objective of the set cover strategy is to minimize the number of cameras while ensuring maximum area is covered. The set packing strategy is based on minimizing the camera coverage overlap while the camera coverage remains in the specified rectangular boundary area. It is hypothesized that set packing strategy is better than set cover strategy with an accuracy of area covered is better than 90%. This is because the set packing strategy is formulated as a nonlinear problem. Thus, the cameras are able to move continuously compared to the set cover strategy which formulated as a linear problem using a discrete interval and binary integer. These strategies then be evaluated iteratively and by means of computer of simulation. The criteria of success are based on the maximum area coverage and minimum coverage overlap. Three different graphic user interface (GUI) which are made available freely for research purposes are modified and used in this study for fair comparison. The results show the set cover strategy is able to cover 91% and set packing is able to cover 93% of the observation area. The percentage of area coverage in the set packing strategy is improved by 2% compared to the set cover strategy according to the condition that had been outlined for both strategies.